Karriere in einer Firma ohne Organigramm: Interview mit Giorgio Curradini (Maurice E. Müller und die Entwicklung künstlicher Hüftgelenke in der Schweiz. Zeitzeugenbefragungen zur Geschichte einer Medizintechnik, 2023)
A trained businessman, Giorgio E. Curradini joined Protek AG in 1976 as an accountant. In 1980, the Board of Directors officially appointed him as a member of the Executive Board, and in 1983 as Deputy Director. Curradini remained responsible for accounting and was in charge of sales in Italy and France. From 1988 to 1992, he managed Protek AG as Director and in 1992 and 1993 as Delegate of the Board of Directors. In 1993, Curradini left the company, which by then belonged to Sulzer Brothers Ltd, but remained active in the prosthesis business. Maurice E. Müller had transferred the distribution rights of Protek AG in Italy to him. From 1993 to 1997, Curradini was CEO of Italpro SPA, which distributed the prostheses of Protek AG and Sulzer Medica in Italy. In the course of the merger of Protek AG and Allo Pro AG, Sulzer Medica AG insisted on the sale of Italpro SPA to it. Curradini became active for Sulzer Medica. After Zimmer took over the company, which had since been renamed Centerpulse, in 2004, Curradini moved to Plus Orthopedics. In 2007 and 2008, he was General Manager of the orthopaedics division of Smith & Nephew in Milan. In 2009, he founded the company Examedical srl in Milan, which develops prostheses and supports the G. I. C. C. A. (Gruppo italiano di chirurgia conservativa dell'anca) foundation.